Wasilija Malinowskiego rozważania (nie tylko) o pokoju i wojnie (czasopismo „Осенние вечера”, 1803 r.) - Dąbrowska, Magdalena (Studia Rossica Posnaniensia, 2016)
The article presents the periodical “Fall Evenings” (1803) by Vasily Fedorovich Malinovsky (1765–1814) in the light of the themes (two thematic lines: political and moral), and particularly the connections (similarities and differences) with the themes of the series of sketches “A Russian in England...” and the treatise Thoughts on War and Peace.